Do microplastic contaminated seafood consumption pose a potential risk to human health?. (October 2021) - Vital, S.A.; Cardoso, C.; Avio, C.; Pittura, L.; Regoli, F.; Bebianno, M.J.
Abstract: Microplastics are present in all parts of the ocean and can have deleterious effects on marine resources. The aim of this work was to map the presence of microplastics in commercial marine species such as bivalves (mussels Mytilus galloprovincialis and clams Scrobicularia plana ), crabs ( Carcinus maenas ) as well as fish ( Mullus surmuletus ) to relate microplastics levels to pollution sources, assess possible impact on marine food chains and on human health. These species were collected from several sites of the Ria Formosa lagoon and along the south coast of Portugal. A quantitative assessment (number, size and color) and typology of microplastics were made in these species. Only one green fragment of polypropylene was detected in the gills of the crabs, while a blue polyethylene fragment was detected in the hepatopancreas of the mullets. Moreover, no microplastics were present in S. plana nor in the crabs whole soft tissues. Among mussels, 86% of microplastics were present from all sites and the number, size and color were site specific. Mussels from the west side of the coast (Sites 1–3) had the highest levels of MPs per mussel and per weight compared to the other sites, probably related to the impact of touristic activity, fishing gears, fresh water and sewage effluents along with the hydrodynamics of the area. Graphical abstract: Unlabelled Image Highlights: Mussels were the most contaminated species by microplastics. Microplastics contamination was related with the extent of nearby seaport and urban areas. Blue was the most common color of microplastics ingested by mussels.